Peran Investment Opportunity Set dalam Memoderasi Faktor-Faktor yang Mempengaruhi Nilai Perusahaan - Rahma, Zamruda; Maryanti, Eny (Owner : Riset dan Jurnal Akuntansi, 2024)
The objective of this study is to assess and examine how the company's value is influenced by factors such as sustainability reporting, capital structure, and cash flow volatility. The study also explores how the investment opportunity set serves as a moderating factor in this relationship. This research employs a quantitative approach, focusing on companies within the mining sector listed on the Indonesia Stock Exchange during the period from 2018 to 2021. The sample selection was carried out using purposive sampling, resulting in a final sample size of 13 companies meeting the predefined criteria. The collected data was subjected to analysis using both multiple linear regression and Moderate Regression Analysis (MRA), utilizing the SPSS 26 software application. The findings of this investigation reveal that sustainability reporting contributes positively to a company's value. In contrast, neither capital structure nor cash flow volatility exhibits a significant influence on company value. Moreover, the study demonstrates that the investment opportunity set acts as a moderating variable, affecting the impact of sustainability reports, capital structure, and cash flow volatility on company value. The conclusions drawn from this study offer insights to potential investors, providing them with valuable considerations when assessing the factors impacting a company's value prior to making investment decisions.